Analisis Semiotika Pesan Komunikasi Ekonomi Politik Pendiri Bangsa dalam Pelaksanaan Pasal 33 UUD 1945 - Marthadinata, Suryadi; Zulkarnain, Iskandar (Jurnal Disrupsi Bisnis, 2024)
"This research aims to find out the semiotic analysis of the political economic communication messages of the founding fathers of the nation contained in the implementation of article 33 of the 1945 Constitution." The data collection technique used by researchers to collect data uses the documentation method, namely tracing various sources such as theses, journals, articles, books and certain notes related to the research theme. This research uses a descriptive qualitative methodology in the form of a literature study using a critical paradigm using Ferdinand De Saussure's semiotic theory. The results of this research are (1) From a political economic perspective, the Indonesian economy must be structured jointly by the state through the government, private sector, cooperatives and society on the basis of the principle of kinship where the state is the leader in decision making. (2) From a political economic point of view, the State must be able to create BUMN and Ministries for important production branches that are directly related to people's livelihoods and ensure that the supply chain is unbroken and the prices are affordable for all levels of society. (3) From a political economic point of view, the State must ensure the security of land ownership for all parties, including traditional communities, civil society, the private sector, as well as the state itself, in accordance with applicable rights and laws. The state must be able to provide land for residence to its citizens who do not own land in accordance with adequate portions of their needs. The state must control clean water sources for household needs and the state must control and own shares in mining companies with a portion of more than 50 percent of the total mining wealth in Indonesia. The state must have complete ownership of half of all the total number of mines in Indonesia to be managed by the nation's children themselves for the prosperity of the Indonesian people.